Can cluster development programmes ensure decent work? Evidence from Indian MSE clusters in global value chains - Vijayabaskar, M. (2008)
Clusters of micro and small enterprises (MSEs) are increasingly seen by policy-makers and multilateral agencies as possible growth engines and employment generators in the current globalising environment. Several policy initiatives seek to build the capabilities of these enterprises to help them compete in the global market. it is implicitly assumed that competing through improved quality and product innovation will lead to better employment outcomes as well. This paper, based largely on secondary literature on globalising clusters specialising in key export sectors, evaluates the links between success in the global product markets, on the one hand, and the quality of work and employment, on the other. It contents that the relationship between the two need not necessarily be a positive one. Improvements in the quality of work, it argues, require interventions of a different order as compared to those aimed at improving the competitiveness of MSEs. - Reproduced.
Keywords: Employment - India; Employment